Commercial Gentrification in the Context of Super-Diversity? the Transformation of Local Streets Shops in Santiago de Chile, Downtown and Pericenter [¿Gentrificación Comercial en Contexto de Superdiversidad?: La Transformación del Comercio Local en el Centro y Pericentro de Santiago de Chile] - Catalan-Hidalgo, R (Universidad de Chile, 2020)
This research focuses on the material transformations of the local street shops in Santiago de Chile downtown and pericenter. Its focus is on the joint process of commercial gentrification and super-diversity, which can configure the specific geography of the transformation that gentrification is producing in Santiago. Two analytical tools are used: firstly, a Gentrification Potential Indicator for selecting the areas with the highest gentrification potential. Subsequently, a visual analysis allows us to understand the recent transformations of local street shops. Six trends that have been transforming local street shops were identified. These changes express the joint effect of commercial gentrification and super-diversity and show the particular character of the urban transformation that Santiago is undergoing and provide a different perspective for the study of gentrification in Santiago. © 2020 Universidad de Chile. All rights reserved.